Detailed description of Division I ice hockey concussions: Findings from the NCAA and Department of Defense CARE Consortium - Kathryn L. Van Pelt; Jaclyn B. Caccese; James T. Eckner; Margot Putukian; M. Alison Brooks; Kenneth L. Cameron; Megan N. Houston; Matthew A. Posner; Jonathan C. Jackson; Gerald T. McGinty; Cameron J. Hillis; Thomas W. McAllister; et al. (Elsevier, 2021)
Objective: Since concussion is the most common injury in ice hockey, the objective of the current study was to elucidate risk factors, specific mechanisms, and clinical presentations of concussion in men's and women's ice hockey. Methods: Ice hockey players from 5 institutions participating in the Concussion Assessment, Research, and Education Consortium were eligible for the current study. Participants who sustained a concussion outside of this sport were excluded. There were 332 (250 males, 82 females) athletes who participated in ice hockey, and 47 (36 males, 11 females) who sustained a concussion. Results: Previous concussion (odds ratio (OR) = 2.00; 95% confidence interval (95% CI): 1.02‒3.91) was associated with increased incident concussion odds, while wearing a mouthguard was protective against incident concussion (OR = 0.43; 95%CI: 0.22‒0.85). Overall, concussion mechanisms did not significantly differ between sexes. There were specific differences in how concussions presented clinically across male and female ice hockey players, however. Females (9.09%) were less likely than males (41.67%) to have a delayed symptom onset (p = 0.045). Additionally, females took significantly longer to reach asymptomatic (p = 0.015) and return-to-play clearance (p = 0.005). Within the first 2 weeks post-concussion, 86.11% of males reached asymptomatic, while only 45.50% of females reached the same phase of recovery. Most males (91.67%) were cleared for return to play within 3 weeks of their concussion, compared to less than half (45.50%) of females. Conclusion: The current study proposes possible risk factors, mechanisms, and clinical profiles to be validated in future concussions studies with larger female sample sizes. Understanding specific risk factors, concussion mechanisms, and clinical profiles of concussion in collegiate ice hockey may generate ideas for future concussion prevention or intervention studies.